Implementation of 23Na MRI - Prestwich, Benjamin (2022)
Sodium magnetic resonance imaging (23Na MRI) has the potential to provide insight into cellular, tissue and organ health. Proton (1H) MRI is well established, but 23Na MRI faces several challenges, principally due to the low inherent 23Na signal from the body and the need for specialist hardware. The aim of this thesis was to lay the groundwork for carrying out 23Na MRI in humans on a clinical MRI scanner, to determine quantitative 23Na measures in the kidneys, muscle and skin.